Exercise performance in young patients with complete atrioventricular block: the relevance of synchronous atrioventricular pacing. (22nd January 2016) - Gonzalez Corcia, M. Cecilia; Remy, Lorraine Saint; Marchandise, Sebastien; Moniotte, Stephane
Abstract: At present, there are many pacing strategies for young patients with complete atrioventricular block. The most frequent policy is to attempt placing a dual-chamber system when possible; however, there is a group of patients that is functioning with a non-synchronous ventricular pacing, raising the question of the ideal timing to upgrade their systems. We investigated the exercise performance of a group of children and young adults with complete atrioventricular block and dual-chamber pacemakers in both single- and dual-chamber pacing modalities. A total of 15 patients performed maximal exercise stress testing after programming the VVIR or DDD modes with 2 hours of interval in a double-blind study protocol. Compared with VVIR pacing, DDD pacing resulted in increase in the peak VO2, longer test duration, major increase in the heart rate achieved during peak exercise, decreased systemic non-invasive arterial blood pressure measured at maximal exercise, higher maximal workload, prolongation of the anaerobic threshold timing, and better self-rated performance perception in all the patients. Synchronous atrioventricular pacing contributes to an increase in both the exercise performance and the performance perception in 100% of the patients. This difference contributes to create a sense of "fitness" with repercussions in the overall health, self-esteem, and life quality, as well as encourages youngster to practice sports. Our experience tends to favour upgrading patients' systems to dual-chamber systems before reaching the adolescent years, even if the centre policy is to prolong as long as possible the epicardial site in order to avoid long years of right ventricular pacing.